Hybrid MPPT Solution for Double-Stage Photovoltaic Inverter - Gomes de Brito, Moacyr Aureliano; Alves, Marcos G. [UNESP]; Canesin, Carlos A. [UNESP] (Springer, 2019)
This paper presents a hybrid MPPT solution applied at a photovoltaic (PV) distributed generation system. The used single-phase power converter is based on the cascaded association of ZVT boost converter and H6-type inverter, considering grid-tie connection in low voltage. The designed 4.8kW rated prototype, which is fed by PV panels association, may require boost voltage during daylight period (sunset/sunrise) or during partial shading scenario. However, due to its nominal current values, the resonant ZVT boost converter presents great advantages, considering its low electromagnetic emission, as well as high efficiency values. Furthermore, the H6-type inverter allows the design of grid connecting elements with reduced volume and weight, besides providing low common mode voltage for the PV system. The hybrid MPPT solution consists of an alternative MPPT that may work resident at the DC-DC stage or at the DC-AC stage, depending on the input voltage and it permits the overall system efficiency to increase. Finally, analysis and experimental results are presented, considering the main control algorithms for the application in order to attend IEC standard.
Keywords: ZVT boost; H6 inverter; Hybrid MPPT; Photovoltaic energy